Cases on building quality distance delivery programs : strategies and experiences - Huffman, Stephanie, 1969- (Hershey, PA : Information Science Reference, 2011)
'This book targets pressing needs in distance education by connecting theory and practice, addressing emerging leadership issues, and identifying best practices in teaching and learning'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Distance education -- Administration; Educational leadership